2022
DOI: 10.1183/23120541.00596-2021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neutrophil extracellular trap formation in COVID-19 is inhibited by the protein kinase C inhibitor ruboxistaurin

Abstract: Background.Neutrophil extracellular traps (NETs) are web-like DNA and protein lattices which are expelled by neutrophils to trap and kill pathogens, but which cause significant damage to the host tissue. NETs have emerged as critical mediators of lung damage, inflammation and thrombosis in COVID-19 and other diseases, but there are no therapeutics to prevent or reduce NETs that are available to patients.Methods.Neutrophils were isolated from healthy volunteers (n=9) and hospitalised patients with COVID-19 at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Neutrophil-soluble mediators, such as elastase and calprotectin, accumulate in plasma of patients with severe disease ( 29 , 30 ). Furthermore, NETs are elevated in the plasma of severe patients and correlate with lung failure and immunothrombosis ( 25 , 31 , 32 , 33 Preprint ), whereas isolated neutrophils from COVID-19 patients display elevated rates of both ROS production ( 34 ) and NETosis ( 35 , 36 ). Several studies have also reported expansion of low-density ( 37 ) and immature (CD10 low ) neutrophils ( 30 , 38 , 39 Preprint , 40 ), whose role in disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-soluble mediators, such as elastase and calprotectin, accumulate in plasma of patients with severe disease ( 29 , 30 ). Furthermore, NETs are elevated in the plasma of severe patients and correlate with lung failure and immunothrombosis ( 25 , 31 , 32 , 33 Preprint ), whereas isolated neutrophils from COVID-19 patients display elevated rates of both ROS production ( 34 ) and NETosis ( 35 , 36 ). Several studies have also reported expansion of low-density ( 37 ) and immature (CD10 low ) neutrophils ( 30 , 38 , 39 Preprint , 40 ), whose role in disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear localization of TFEB induced by PKC-α/δ occurs via GSK3β in mTORC1-independent manner ( 30 ). Additionally, an orally active PKC inhibitor ruboxistaurin proves to be active against SARS-CoV-2 as it inhibits NETosis, and has passed phase 3 for other indications ( 71 ). Previous studies have also shown that ruboxistaurin was active against GSK3α and GSK3β with IC 50 values of 695.9 nM and 97.3 nM, respectively ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…S1-7). Neutrophils also play a critical role in hyperinflammation [146][147][148][149][150][151][152][153][154][155] . Activated neutrophils release NETs and ROS to eradicate bacteria 156 .…”
Section: Discussionmentioning
confidence: 99%